Multimedia communications, services and security : 8th International Conference, MCSS 2015, Kraków, Poland, November 24, 2015, proceedings /: 8th International Conference, MCSS 2015, Kraków, Poland, November 24, 2015, proceedings. (2015) - Unknown
No abstract available